A Study on the Index of Index of Internet Financial Reporting - Ali Khan, Mohd Noor Azli; Ismail, Noor Azizi (UUM Press, 2010)
Innovation in the usage of information technology and communication (ICT) has set up a unique method in corporate management which includes distributing financial report direct to the investors, prospective investors, share holders and important personnel. As it is consistent to the internet development as a form of cheap and flexible but influential communication tools, exposures of financial information through the internet has gain its popularity as one of a famous research subject. The last decade has seen a lot of research been carried out on the significance, method and quality of internet financial reporting (IFR). However, most of the earliest IFR research were inclined towards descriptive and exploration methods. Thus, the researches fail to explain items that represent the level of IFR. Even though most of the research bowed to the fact that matching proxy such as disclosure index could assist fuller depth of understanding of the sophisticated information disclosed by companies, it is undeniable that very little effort are taken to build the reporting index. The limited literature shows that there are inconsistencies in the usage of dimensions that represent IFR among researchers. As the result there are differences in the output which lead to the findings failure in giving clear explanation on the factors that influence IFR behaviors. Therefore, this article will discuss issues connected to index of IFR by viewing the related literature, comprehensively, before suggesting a dimension that compliment disclosure index which represent IFR.